Karakteristik telur dan DOC ayam bangkok generasi pertama (G1) : Characteristics of first generation (G1) bangkok chicken eggs and DOC - Ilham Wahyudi; Depison - Depison; Silvia Erina (Fakultas Peternakan Universitas Papua, 2022)
Abstract The study aims to determine the relationship between egg characteristics and egg weight, DOC weight and body weight, to characterize the size and body shape of the first generation of Bangkok chickens aged 3 months. A total of 315 chicken eggs were used with the experimental method. Characteristics of eggs, egg weight, body weight, weight gain and body measurements, DOC weight and characters of weight and body shape were analyzed using a t-test. regression and correlation analysis and principal component analysis. T-test showed chicken males were higher than females (P<0.05). Egg characteristics are positively related to egg weight with a correlation value of 66.90% for males and 84.10% for females. DOC weight of male and female chickens was positively related to body weight at 1, 2 and 3 months of age, with correlation values of DOC weight with roosters respectively 73.40%, 67.90% and 65.10% and females 74.20%, 67 .00% and 52.40%. The body size characteristic of male and female chickens is chest circumference. The characteristic body shape of the rooster is the wing's length while the hen is the length of the upper body. Conclusion: there is a positive relationship between egg characteristics and egg weight and the highest correlation between egg girth and egg weight, DOC weight with body weight with the highest correlation at 1-month weight, the identifier of body size is chest circumference and body shape characteristics, is the wing length (male) and upper body length (female). Keywords: Bangkok chicken; Body weight; Characteristics of eggs; Correlation; Regression Abstrak Penelitian ini bertujuan 1) mengetahui hubungan karakteristik telur dengan bobot telur, 2) bobot DOC dengan bobot badan, 3) penciri ukuran dan bentuk tubuh ayam Bangkok generasi pertama umur 3 bulan. Sebanyak 315 butir telur ayam Bangkok digunakan dalam penelitian ini dengan metode eksperimen. Karakteristik telur, bobot telur, bobot badan, pertambahan bobot badan dan ukuran-ukuran tubuh dianalisis menggunakan uji-t. Hubungan karakteristik telur dengan bobot telur, dan bobot DOC dengan bobot badan umur DOC-3 bulan diuji menggunakan analisis regresi dan korelasi. Penciri ukuran dan bentuk tubuh dianalisis menggunakan analisis komponen utama. Karakteristik telur, bobot telur, bobot DOC, bobot badan, dan pertambahan bobot badan serta ukuran-ukuran tubuh ayam Bangkok jantan lebih tinggi dibandingkan ayam betina (P<0,05). Karakteristik telur berhubungan positif dengan bobot telur dengan nilai korelasi pada jantan 66,90% dan betina 84,10%. Bobot DOC ayam jantan dan betina berhubungan positif dengan bobot badan umur 1, 2 dan 3 bulan, dengan nilai korelasi bobot DOC dengan ayam jantan berurutan 73,40 %, 67,90 % dan 65,10% dan betina 74,20%, 67,00% dan 52,40%. Penciri ukuran tubuh ayam jantan dan betina yaitu lingkar dada. Penciri bentuk tubuh ayam jantan yaitu panjang sayap sedangkan ayam betina yaitu panjang tubuh atas. Kesimpulan: 1) terdapat hubungan yang positif antara karakteristik telur dengan bobot telur dan korelasi tertinggi antara lingkar telur dengan bobot telur, 2) bobot DOC memiliki hubungan yang positif dengan bobot badan dengan korelasi tertinggi bobot 1 bulan, 3) Penciri ukuran tubuh yaitu lingkar dada dan penciri bentuk tubuh yaitu panjang sayap (jantan) dan panjang tubuh atas (betina). Kata Kunci: Ayam Bangkok; Bobot Badan; Karakteristik Telur; Korelasi; Regresi